APLIKASI RESERVASI MEETING ROOM BERBASIS WEB(STUDI KASUS: PT PERTAMINA EP - Mohammad Faudzan Azizun Hakim (2021)
This makes it difficult to order the availability of meeting room services for internal parties, it also becomes difficult for the admin in arranging available meeting rooms, and the lack of information shared with users regarding the availability of meeting rooms and the number of meeting rooms. The information expected for the user is more visual and interactive as well as the certainty of the availability of meeting rooms so that it is more efficient and attractive for users who want to make a meeting room reservation, and convenience for the admin in m. For this reason, a website-based ordering service information system is needed to make it easier for customers to place an order and also make it easier for administrators to manage available meeting rooms. The author uses the waterfall method which includes Requirement Analysis, System Design, Program Code Writing, Program Testing and Maintenance. The programming language used by the author is PHP which is supported by MySql as a database. The system analysis method uses PIECES and uses UML (Unified Modeling Language) modeling. The results of this study are programs to make meeting room reservations, which can also be used by the admin in arranging available meeting room reservations.